A leaf wax and small metabolites from the leaves of alphonsea cylindrica - Mohd Azlan Nafiah (Tanjung Malim, 2023)
A leaf wax and small metabolites from the leaves of alphonsea cylindrica by Mohd Azlan Nafiah